Study Of the Villages in Mullaitivu District Which Are Named According to The Medicinal Plants - Sathyaseelan, V.; Atavan, V. (Institute of Indigenous Medicine University of Colombo, Rajagiriya Sri Lanka, 2015)
There are various type of medicinal plants available in Sri Lanka. The life style of ancestors in Sri Lanka were closely related with nature. It must be noted that they have used the names of medicinal plants to name villages and reservoirs. Objective of the study is to identify villages in Mullaitivu district which are named according to the medicinal plants. Frequent field visits were made to the areas during January 2014-July 2014. The data was collected directly visiting the areas and conducting interview with people who resides there. Mullaitivu district consists six divisional secretariats and 136 Grama niladhari divisions. 611 villages are in the divisions. The results revealed 90 villages are named based on the medicinal plants. Of these 90 villages, 54 (60%) villages are named based on trees, 16 (17.77%) villages are named based on shrubs, 15 (16.66%) villages are named based on herbs, and 2 (2.22%) villages are named based on costal plants. In the medicinal plants names, 8, medicinal plants are used in diabetic mellitus, 20 medicinal plants used in skin diseases, 12 medicinal plants used in arthritis 10 medicinal plants used in respiratory disorders and 11 medicinal plants used in gastro intestinal disorders. These plants belongs to the families named Leguminosae, Acanthaceae, Bambusaceae, Loganiaceae, Malvaceae, Moraceae, Oleaceae, Pandanaceae and Rubiaceae family. Plants without any use will not be concerned by anybody. Therefore adequate knowledge should be important to the general public who are living to the study area on sustainable use by identified medicinal plants named to the villages. We must take immediate action to recultivating plant which are going to verge of extension and also obtained available information on medicinal plants.
Keywords: Medicinal plants; Mullaitivu district; Villages